CONFIDENTIALITY AND AVAILABILITY OF SECURITY MEASURES FOR INFORMATION SYSTEMS IN UNIVERSITIES IN KISUMU AND SIAYA COUNTIES, KENYA - Musyoka, Martin M. N.; Raburu, George; Yoga, Castro; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
Many organizations continue to grow in numbers by the day in adopting use and adoption of ICTin day to day business processes and so are the rising trends in cyber insecurity. Securinginformation systems against myriad spectrum of threats requires use of multiple, overlappingprotection approaches addressing people, technology and operational processes. ICT policies areput in place in institutions to provide guidelines and standards on what is acceptable and what isnot as regards to use of ICT systems. In spite of these ICT policies, numerous instances all overthe world have been reported whereby university systems were compromised and universityinformation exposed to other third parties or malicious activities or unintentional errors.According to a report published by Oracle (2008), there have been hundreds of data breachescosting millions of dollars and damaging universities’ reputation. There is no evidence thatresearch has been carried out in the past to assess the level of compliance to ICT security policiesby the institutions of higher learning. This study therefore sought to bridge this gap by means ofa survey, to investigate and describe the level of compliance to ICT security policies in terms ofconfidentiality and availability in Universities in Kisumu and Siaya Counties, Kenya